2014
DOI: 10.1111/jmwh.12199
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Evidence‐Based Practices for Management of the Second Stage of Labor

Abstract: Management of the second stage of labor often follows tradition-based routines rather than evidence-based practices. This review of second-stage labor care practices discusses risk factors for perineal trauma and prolonged second stage and scrutinizes a variety of care practices including positions, styles of pushing, use of epidural analgesia, and perineal support techniques. Current evidence for management of the second stage of labor supports the practices of delayed pushing, spontaneous (nondirected) pushi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 82 publications
2
36
0
7
Order By: Relevance
“…Specifically, women who delayed pushing had an average total second stage that was longer shown by an adjusted mean difference of 107.2 minutes (95% CI 105.1-109. 3) and an average total time actively pushing that was longer shown by an adjusted mean difference of 10.4 minutes (95% CI 8.5-12.3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, women who delayed pushing had an average total second stage that was longer shown by an adjusted mean difference of 107.2 minutes (95% CI 105.1-109. 3) and an average total time actively pushing that was longer shown by an adjusted mean difference of 10.4 minutes (95% CI 8.5-12.3).…”
Section: Resultsmentioning
confidence: 99%
“…While the American College of Obstetricians and Gynecologists has no explicit position statement on delayed pushing, midwifery and some obstetric literature recommend consideration of delayed pushing for one to two hours, or until the woman experiences the urge to push, for appropriate patients. [2][3][4] Similarly, the International Federation of Gynecology and Obstetrics recommends waiting up to four hours for the nulliparous women to experience the urge to push before initiating active pushing. 5 While a long second stage 6,7 and prolonged active pushing in the second stage 8 have been associated with an increased risk of adverse maternal and neonatal outcomes, data on the maternal and neonatal risks associated with delayed pushing are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…3,54 With better ability for intrapartum fetal monitoring, some clinicians propose that waiting for a strong urge to push can maximize the efficiency of maternal expulsive effort and reduce risk of maternal exhaustion and need for operative delivery. 53,55 In addition to epidural analgesia potentially affecting maternal expulsive effort and efficiency, some studies suggest that epidural analgesia may be associated with fetal head malposition (eg, occiput posterior or transverse position) at delivery as a result of fetal occiput malrotation during labor. [56][57][58] One study that evaluated changes in fetal position during labor using serial ultrasound examination reported that regardless of fetal head position early in labor, final fetal position is established close to delivery.…”
Section: Impact Of Epidural Analgesiamentioning
confidence: 99%
“…This has been observed elsewhere. 6,9,10 For prevention or correction of VM, more studies, such as specific maternal positions to be adopted during labor, should be carried out especially among the sub-Saharan women, given the poor maternal and neonatal outcomes associated with VM.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Manual rotation may correct the malposition. 10,14 No recent study to our knowledge has evaluated the outcome of labor in cases of VM in sub-Saharan women. Hence, this study was aimed at evaluating labor outcome in such women.…”
Section: Introductionmentioning
confidence: 99%